Fracturing and calcite cementation controlling fluid flow in the shallow-water carbonates of the Jandaíra Formation, Brazil. (February 2017) - de Graaf, Stefan; Reijmer, John J.G.; Bertotti, Giovanni V.; Bezerra, Francisco H.R.; Cazarin, Caroline L.; Bisdom, Kevin; Vonhof, Hubert B.
Abstract: The shallow-marine carbonate rocks of the Jandaíra Formation have been subject to significant permeability variations through time due to various events of fracturing and calcite cementation. As a consequence, the Jandaíra Formation accommodated fluid flow only during specific moments in time. We reconstructed these episodes of fluid flow based on isotope characterizations and microscope characteristics of calcite veins and host rock cements. The Jandaíra Formation, which belongs to the post-rift sequence of the Potiguar Basin in northeast Brazil, was deposited from the Turonian onward until a marine regression exposed it in the Campanian. Due to the subaerial exposure, meteoric waters flushed out marine connate waters, leading to an event of early diagenesis and full cementation of the Jandaíra Formation. Fluid flow through the resulting impermeable carbonate formation appears to be closely related to fracturing. Fracturing in the Late Cretaceous induced a drastic increase in permeability, giving rise to extensive fluid circulation. Host rock dissolution associated to the circulating fluids led to calcite vein cementation within the fracture network, causing it to regain an impermeable and sealing character. In the research area, fluid flow occurred during early burial of the Jandaíra Formation at estimated depths of 400–900 m. This study documents the first application of fluid inclusion isotope analysis on vein precipitates, which allowed full isotopic characterization of the paleo-fluids responsible for calcite vein cementation. The fluid inclusion isotope data indicate that upwelling of groundwater from the underlying Açu sandstones provided the fluids to the fracture network. In Miocene times, renewed tectonic compression of a lower intensity created a secondary fracture network in the Jandaíra Formation. The density of this fracture network, however, was too low to induce a new episode of fluid circulation. As a result, this tectonic event is associated with the development of barren extensional fractures. Highlights: Isotope data were used to reconstruct paleo-fluid flow within the Jandaíra limestones. Fluid inclusion isotope analysis was applied for the first time on vein precipitates. Fluid flow appeared to be controlled by fracturing and cementation of calcite. Fluid supply happened by upwelling of groundwater from an underlying aquifer. The Jandaíra Formation experienced significant permeability variations through time.